2023
DOI: 10.21037/jtd-23-1042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on pulmonary function in patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease, and its treatment is still controversial. Statins have been proven to have anti-inflammatory and immunomodulatory effects, but their effectiveness in the treatment of COPD is still unclear. We conducted this meta-analysis to more accurately evaluate the therapeutic effect of statins on COPD patients. Methods Randomized controlled studies published in PubMed, Cochrane Library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…W badaniu autorstwa Li i wsp., obejmującym 7566 (kohorta 1) oraz 9294 (kohorta 2) uczestników w średnim wieku -odpowiednio 62 (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) i 65 (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) lat, których obserwowano przez okres 8 lat, także oceniano wpływ ciśnienia tętniczego na ryzyko wystąpienia demencji. Stwierdzono, że wraz ze zwiększeniem skurczowego ciśnienia tętniczego (przedziały kwartylowe) ryzyko wystąpienia demencji wzrastało istotnie o 38-98%.…”
Section: Związek Między Nadciśnieniem Tętniczym a Demencjąunclassified
See 1 more Smart Citation
“…W badaniu autorstwa Li i wsp., obejmującym 7566 (kohorta 1) oraz 9294 (kohorta 2) uczestników w średnim wieku -odpowiednio 62 (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) i 65 (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) lat, których obserwowano przez okres 8 lat, także oceniano wpływ ciśnienia tętniczego na ryzyko wystąpienia demencji. Stwierdzono, że wraz ze zwiększeniem skurczowego ciśnienia tętniczego (przedziały kwartylowe) ryzyko wystąpienia demencji wzrastało istotnie o 38-98%.…”
Section: Związek Między Nadciśnieniem Tętniczym a Demencjąunclassified
“…również zaobserwowali, że stosowanie walsartanu (160 mg) wraz z amlodipiną (10 mg) było związane ze zmniejszeniem PP i PWV [64]. Warto też wspomnieć o wynikach metaanalizy 10 randomizowanych badań klinicznych, którą przeprowadzili Chen i wsp., w której stwierdzono, że sartany (reprezentowane głównie przez walsartan) wykazywały się największym spośród innych klas leków przeciwnadciśnieniowych wpływem na obniżenie współczynnika wzmocnienia (AI, augmentation idex), który jest wykładnikiem sztywności naczyń (p = 0,01) [65].…”
Section: Wpływ Na Ciśnienie Tętna I Prędkość Fali Tętnaunclassified
“…There have been numerous studies evaluating various pulmonary arterial hypertension (PAH) therapies in COPD patients, but most of these have been small, open-label or retrospective. Nonetheless, two meta-analyses of these trials have suggested a treatment benefit [ 4 , 5 ]. There have been very few randomised controlled studies for PH-COPD; one small study of sildenafil was positive, but a larger study of tadalafil was negative [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…With a combination of targeted drugs (3) such as phosphodiesterase-5 inhibitors, endothelin receptor antagonists, prostacyclin analogs, and prostacyclin receptor agonists, patients with pulmonary arterial hypertension (PAH, i.e., WHO group I PH) have shown a significant improvement in activity tolerance and disease prognosis. However, clinical trials of these drugs have not shown any beneficial effects in patients with HPH (4,5). Therefore, clarifying the underlying pathogenic mechanisms in this group of patients will help to improve targeted therapies.…”
Section: Introductionmentioning
confidence: 99%